Studi Deskriptif Kualitatif : Fenomena Nomophobia Mahasiswa di Yogyakarta - Khoiryasdien, Andhita Dyorita; Ardina, Mega (Prosiding University Research Colloquium, 2020)
This study aims to obtain a description of the condition of nomophobia among college students in Yogyakarta. This research was conducted by discussing descriptive qualitative. The number of subjects in this study were 48 students studying in Yogyakarta. Data collection techniques using observation ,interviews and surveys based on Nomophobia theory. The results showed that 100% of students have social media applications and short message applications that are used every day. Students feel anxious when they can’t connect to the internet so they can’t access information and communicate. Students still carry smartphones wherever they go even to the toilet. The habit that ultimately causes students to experience nomophobia is to always access the smartphone all the time and feeling lazy to do other activities. When they are confused about what to do, students choose to find entertainment through smartphones.